1992
DOI: 10.1002/bms.1200211102
|View full text |Cite
|
Sign up to set email alerts
|

Determination of (22R,S)budesonide in human plasma by automated liquid chromatography/thermospray mass spectrometry

Abstract: (22R,S)Budesonide was isolated from human plasma by solid-phase extraction. Switching from reversed-phase conditions during sample application and washing to normal-phase conditions during elution afforded a very clean extract. Budesonide was derivatized with acetic anhydride to form the 21-acetyl derivative before analysis by reversed-phase liquid chromatography combined with thermospray mass spectrometry. Deuterium-labelled budesonide was used as internal standard. Standard samples prepared in human albumin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The plasma was separated by centrifugation (1,500×G) for 10 min and was then immediately frozen at -20°C until analysed. The assay of budesonide in plasma was based on a combination of liquid chromatography and mass spectrometry (LC-MS) [8].…”
Section: Methodsmentioning
confidence: 99%
“…The plasma was separated by centrifugation (1,500×G) for 10 min and was then immediately frozen at -20°C until analysed. The assay of budesonide in plasma was based on a combination of liquid chromatography and mass spectrometry (LC-MS) [8].…”
Section: Methodsmentioning
confidence: 99%
“…The plasma was separated by centrifugation (1500×g) for 10 min and was then imme-diately frozen at -20°C until analysis. The assay of budesonide in plasma was based on a combination of liquid chromatography and mass spectrometry [12].…”
Section: Methodsmentioning
confidence: 99%
“…Also, the presence of the two angular methyl groups on the steroid backbone should provide considerable steric hindrance to sulfation of the 11-hydroxyl group. In accordance with these observations, it has been shown that budesonide and hydrocortisone can be selectively acetylated chemically at the 21-hydroxyl group without affecting the more sterically hindered 11␤-hydroxyl group (Paulson and Lindberg, 1991;Lindberg et al, 1992). Moreover, budesonide is known to be conjugated with fatty acids in lung and liver apparently at the 21-hydroxyl group (Tunek et al, 1997).…”
Section: Meloche Et Almentioning
confidence: 84%